Eficacia del tratamiento con dos clavos de Rush en las fracturas diafisiárias de fémur en niños - Cesías López, Víctor Manuel (2010)
To determine if the processing of pegged intra central with two semi-stiff nails of Rush is more efficient than the cutaneous traction of Russell plus gypsum pelvi pedio, in the closes diafisarias fractures of femur in children. Material and methods: I carried out a prospective study experimental type of cases and controls in the ―Hospital II‖ of Tarapoto among Nov. 2008 and Nov. 2009. 12 children were assigned randomly in two groups. To the group 1 (6 controls) I applied the processing of cutaneous traction followed by immobilization with gypsum pelvi pedio and to the group 2 (6 cases) the pegged intra central with two semi-stiff nails of Rush. Results: In the follow-up of the 3rd and 6th month, in the 100% of the cases of the group 2, good results were obtained, being these statistically significant results upon being applied the test T of student. Conclusions: The pegging intra central semi-stiff with two nails of Rush is more efficient than the traction cutaneous followed by gypsum pelvi pedio in the processing of the closes fractures diafisarias of femur in children, measures through the early functional result